The Impact of Card Media on the Students’ Ability in Writing Descriptive Text in Senior High School - Fita Faridah; Afifatus Sa’diyah (ELITE JOURNAL, 2023)
This study aims to know about the influence of card media on the student’s ability in writing descriptive text of tenth-grade students in senior high school. This study was designed as a pre-experimental with one group pretest-posttest. The population used in this study was the 10th-grade students of MA Nurul Huda Suci as many as 30 students, the researchers used the entire population as a sample. The researcher used a writing test as a data collection technique. In the technique of analyzing the data, the researcher used descriptive statistics and the t-test was in the form of paired sample t-test to test the hypothesis through the SPSS statistic 25 programs. The results of using descriptive statistics showed that the average score of students at the time of the post-test using card media was greater than pre-test scores without using card media (50.87 < 70.43). while the hypothesis test using the paired sample t-test showed a significant (2-tailed) value of 0.00 < 0.05, meaning that Ha was accepted and H0 was rejected. From the results of statistical descriptive tests and hypothesis testing using paired sample t-test, it can be concluded that there is an influence between card media and students' ability to write a descriptive text. Keywords: Card Media, Descriptive Text, Students’ Ability, Writing